2015
DOI: 10.1210/jc.2015-1453
|View full text |Cite
|
Sign up to set email alerts
|

The Gene of the Ubiquitin-Specific Protease 8 Is Frequently Mutated in Adenomas Causing Cushing's Disease

Abstract: USP8 is frequently mutated in adenomas causing Cushing's disease, especially in those from female adult patients diagnosed at a younger age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
209
6
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 180 publications
(241 citation statements)
references
References 38 publications
24
209
6
2
Order By: Relevance
“…Previously-reported USP8 mutants loose binding to 14-3-3 proteins, undergo cleavage adjacent to the 14-3-3 binding motif to the 90-and 40-kDa fragments, and the 40-kDa fragment (C40) acquires high DUB activity (9,11). Since the functions of three of the seven USP8 mutants identified in this study (S718F, S719P, and S718_P720delinsT) had not been determined, we performed a functional analysis.…”
Section: Functional Analysis Of Usp8 Mutationsmentioning
confidence: 97%
See 2 more Smart Citations
“…Previously-reported USP8 mutants loose binding to 14-3-3 proteins, undergo cleavage adjacent to the 14-3-3 binding motif to the 90-and 40-kDa fragments, and the 40-kDa fragment (C40) acquires high DUB activity (9,11). Since the functions of three of the seven USP8 mutants identified in this study (S718F, S719P, and S718_P720delinsT) had not been determined, we performed a functional analysis.…”
Section: Functional Analysis Of Usp8 Mutationsmentioning
confidence: 97%
“…S718_P720delinsT was a novel mutation. Others (S718del, P720R, S719P, S718F, P720Q, and P720_D721del) have been previously identified (9,10,11). USP8 mRNA levels were measured using qRT-PCR to determine whether the expression levels of USP8 differed between the USP8 mutants and the WT.…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, this revealed recurrent mutations in the USP8 gene that encodes a deubiquitinase (Perez-Rivas et al 2015, Reincke et al 2015. Although USP8 could have many different substrates (Ge et al 2015), current analyses indicate that corticotroph adenomas with USP8 mutations have persistent EGF signaling.…”
Section: Defective Signaling In Cushing's Diseasementioning
confidence: 84%
“…Perez-Rivas et al (39) demonstrated that somatic mutations comprising p.718Ser>Pro, Ser718del, p.720Pro>Gln, and p.720Pro>Arg in USP8 diminished EGFR ubiquitination and induced the activity of the POMC promoter. Ma et al (40) reported the significant clinical relevance of three somatic mutations (c.CTC2151-2153del/p.S718del, c.C2159G/p.…”
Section: Ubiquitin-specific Peptidase 8 (Usp8) Mutationmentioning
confidence: 99%